Patient Safety Teaching to Our Students. (October 2016) - Sonn, Tammy; Ross, Whitney
Abstract : BACKGROUND: Patient safety understanding and awareness is an important aspect of clinical medicine that should be taught throughout the medical school curriculum. We previously did not have any structured teaching around this topic. METHODS: During the course of our 6 weeks clerkship, we have 2 formal teaching encounters to discuss patient safety. During orientation, students complete a pre-intervention questionnaire and are introduced to 2 areas of focus during a 20 minute talk: OR Patient Safety and the IPASS handoff technique. They are given an assignment requesting them to document 3 examples of patient safety related observations. The second encounter is during week 5 of the clerkship where 1 hour is spent with the following activities: viewing a video clip of a patient safety story (Josie King Story), discussing the assignment, and reviewing the IPASS handoff with role playing. Following this session, the students are given the final post-intervention questionnaire. RESULTS: Students (n=105) felt more comfortable after the new curricular intervention. They felt more aware of medical errors within clinical medicine ( P <.001), felt more familiar with the IPASS handoff to use it ( P <.001), and felt OR patient safety is a comfortable topic to discuss ( P <.001). DISCUSSION: Our patient safety curriculum appears to have a positive impact based on student perception. Feeling more aware of medical errors, being able to use the IPASS handoff, and being comfortable talking about aspects of OR safety are all areas students felt more competent in post-intervention.